Enhancing psychological well-being of school teachers in India: role of energy management, thriving, and stress - Chaudhry, Smita; Chhajer, Raina (Frontiers in Psychology, 2023)
Purpose The psychological well-being of school teachers is a growing concern in the post-pandemic era. Many initiatives are undertaken by individual school authorities and government agencies to address this issue. In this study, we examine the impact of energy management, thriving, and stress on the psychological well-being of school teachers in India. Method Data was collected from 356 school teachers in Rajasthan, India, through a cross-sectional questionnaire survey. These teachers were working both in rural and urban areas. The relationship among energy management, thriving, stress, and psychological well-being was analyzed using hierarchical regression. Results The findings suggest that energy management positively impacts psychological well-being. A mediating effect of thriving and stress on the relationship between energy management and psychological well-being was also found. The results support that psychological well-being can be enhanced by investing in managing school teachers’ energy levels. Discussion These results contribute to our theoretical and practical understanding of factors that can enhance the psychological well-being of school teachers and improve the quality of education. Institutes may design and implement interventions on energy management to enhance the psychological well-being of school teachers.